Material capable of being used for battery positive electrode and application of material in battery
By preparing a new battery additive material with the structure of formula (I), the problems of excessive alkalinity and poor air stability of the existing sodium ion battery positive sodium supplementing agent materials are solved, and efficient sodium supplementation effect and good battery performance are achieved.
Patent Information
- Application Number
- CN202311283540.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The existing sodium ion battery positive sodium supplementing agent materials have problems such as excessive alkalinity on the surface and poor air stability, which leads to abnormal situations such as jelly decomposition of the slurry, coating and film removal, affecting battery performance.
A novel battery additive material has a structure of formula (I), prepared by high temperature sintering of oxides of Fe2O3, Na2O and/or L under specific stoichiometric ratios and temperature conditions, forming a sodium supplementing agent with good air stability and high theoretical specific capacity.
This material can be controlledly synthesized under simple conditions, has good air stability and high theoretical specific capacity, and is suitable for a variety of metal ion secondary batteries, significantly improving the performance and commercial application value of the battery.
Smart Images

Figure CN119725516A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a battery additive material and a preparation method and application thereof. Background Art
[0002] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can be recharged to activate the active materials and continue to be used after the battery is discharged. Sodium-ion batteries and lithium-ion batteries are the two most commonly used secondary batteries on the market. Other metal-ion secondary batteries, such as magnesium-ion batteries and calcium-ion batteries, also show great potential and the possibility of surpassing sodium-ion batteries and lithium-ion batteries in some aspects. Metal-ion secondary batteries have similar working principles and similar problems. For example, taking sodium-ion batteries as an example, when sodium-ion batteries are charged in the first week, a solid electrolyte interface phase (SEI) film will be formed on the surface of the negative electrode, causing irreversible capacity loss of the positive electrode material, thereby affecting the capacity and cycle life of the battery. Therefore, it is necessary to solve this problem through pre-sodiumization (sodium supplementation). Sodium-deficient oxide material Na t MO2 (0<t<1) has a high theoretical reversible capacity, good cycle performance and rate performance, and has great potential as a positive electrode material for sodium-ion batteries. However, the initial sodium content of sodium-deficient materials is insufficient, and the remaining capacity requires additional sodium embedding. Therefore, in practical applications, additional sodium sources are needed to achieve and maintain a high specific capacity, and the required amount of sodium replenishment is large. The pre-sodiumization (sodium replenishment) method can effectively solve this problem. At present, it can be roughly divided into two types: negative electrode sodium replenishment and positive electrode sodium replenishment according to the battery object being treated. Negative electrode sodium replenishment is to use sodium foil, sodium powder, etc. to react chemically / electrochemically with the negative electrode sheet to achieve negative electrode pre-embedded sodium. At present, its large-scale application is limited by factors such as safety, cost and stringent environmental control requirements. Positive electrode sodium replenishment is to add high-capacity sodium-rich materials to the positive electrode sheet to compensate for the loss of active sodium in the negative electrode. Its advantage is that the sodium replenishment material can be directly added to the positive electrode slurry for use, without changing the existing pulping and coating process, which is easy to operate and easy to industrialize. The positive electrode sodium replenishment materials currently reported include organic sodium salts and inorganic sodium replenishment agents. Among inorganic sodium supplement materials, the sodium-rich transition metal oxide type currently has the greatest commercial potential, but most of them have problems such as too high surface alkalinity and poor air stability (easy to absorb moisture and deteriorate). Among them, too high surface alkalinity will lead to the destruction of the binder in the slurry, causing abnormal conditions such as jelly of the slurry and coating delamination; and moisture absorption and deterioration will not only lead to a decrease in the sodium supplement effect, but also affect the moisture control during the battery cell manufacturing process, affecting the overall performance of the battery.
[0003] Therefore, it is necessary to provide an improved battery additive that can overcome the shortcomings of the prior art and provide a higher commercial application value. Advantageously, a sodium supplement is provided that can be controllably synthesized under simple conditions. Advantageously, a sodium supplement is provided that has good air stability. Advantageously, a sodium supplement is provided that has a higher theoretical specific capacity and / or a lower reversible specific capacity. Advantageously, a sodium supplement is provided that has a higher first-cycle irreversible specific capacity. It is also advantageous to provide a battery additive that can be applied to more types of metal ion secondary batteries by replacing part or all of the sodium in the above-mentioned sodium supplement with one or more other alkali metals or alkaline earth metal elements such as lithium, magnesium, calcium, etc. Summary of the invention
[0004] In one aspect, the present invention provides a material having the structure of formula (I):
[0005] Na 7n-x L x Fe 3n-y M y O 8n-a-b R a Q b (I)
[0006] in:
[0007] n is an integer selected from 1 to 10,
[0008] 0≤x≤7n,
[0009] 0≤y<3n,
[0010] 0≤a<8n,
[0011] 0≤b<8n,
[0012] L is one or more elements selected from Group IA and IIA elements in the long-period periodic table,
[0013] M is one or more metal elements selected from Groups IA-VIA, IB-VIIB and VIII in the long-period periodic table,
[0014] R is one or more selected from the elements of Group VIIA in the long-period periodic table, and
[0015] Q is one or more selected from the elements of Group VIA in the long-period periodic table.
[0016] In another aspect, the present invention provides a method for preparing a material of formula (I) according to the present invention, the method comprising the following steps:
[0017] (a) mixing Fe2O3, Na2O and / or an oxide of L, and an optional dopant precursor to obtain a precursor mixture, wherein the stoichiometric ratio between Fe2O3 and the oxide of Na2O and / or L is 1:9-9:1, preferably 1:9-1:1, more preferably 1:6-1:2, wherein L is one or more elements selected from Groups IA and IIA of the long period periodic table;
[0018] (b) heating the precursor mixture at a temperature of 100-1200° C., preferably 200-800° C., for 1-200 hours, preferably 20-100 hours under an inert atmosphere for high temperature sintering;
[0019] (c) After cooling, the material is obtained.
[0020] In yet another aspect, the present invention provides a coated material comprising a core and a coating layer covering the surface of the core, wherein:
[0021] The core comprises a material of formula (I) according to the present invention;
[0022] The coating layer comprises one or more materials selected from the group consisting of metal fluorides, metal carbides, metal oxides, polymers, carbon, and combinations thereof;
[0023] Optionally, there may or may not be a cavity between the coating layer and the core, and optionally, the coating layer is a continuous layer or a discontinuous layer.
[0024] In yet another aspect, the present invention provides a composite material comprising a first material and a second material, wherein:
[0025] The first material comprises a material of formula (I) according to the present invention;
[0026] The second material is a battery active material different from the first material.
[0027] In another aspect, the present invention provides a method for preparing a composite material according to the present invention, the method comprising the step of compounding a first material and a second material in a mixed and / or coated form, wherein the mixing preferably comprises the step of mixing the first material and the second material by stirring and / or grinding, and the coating preferably comprises the step of attaching the second material to the outside of the first material.
[0028] In yet another aspect, the present invention provides a positive electrode active material comprising one or more of the material of formula (I) according to the present invention, the coated material according to the present invention, the composite material according to the present invention, and combinations thereof.
[0029] In still another aspect, the present invention provides a positive electrode for a battery, comprising the positive electrode active material according to the present invention, an optional conductive agent, and an optional binder.
[0030] In another aspect, the present invention provides an electrode sheet or a diaphragm, which comprises one or more of the material of formula (I) according to the present invention, the coated material according to the present invention, the composite material according to the present invention, and a combination thereof; the electrode sheet or the diaphragm preferably comprises a coating, and the coating comprises one or more of the material of formula (I) according to the present invention, the coated material according to the present invention, the composite material according to the present invention, and a combination thereof.
[0031] In still another aspect, the present invention provides an electrochemical device comprising at least one of the positive electrode active material according to the present invention, the battery positive electrode according to the present invention, the electrode sheet or separator according to the present invention, and a combination thereof.
[0032] The present invention provides more possibilities for developing high-performance batteries by providing a new type of battery additive material. The new battery additive material of the present invention can be used, for example, in sodium ion batteries and / or lithium ion batteries as a sodium / lithium supplement additive material. Specifically, the new battery additive material of the present invention can provide one or more of the following advantages: 1) It can be controllably synthesized under simple conditions; 2) It has good air stability; 3) It has a higher theoretical specific capacity and / or a lower reversible specific capacity; 4) It has a higher first-cycle irreversible specific capacity; 5) It can be widely used in a variety of batteries, such as sodium ion batteries, lithium ion batteries, potassium ion batteries, rubidium ion batteries, cesium ion batteries, magnesium ion batteries, calcium ion batteries, strontium ion batteries, barium ion batteries and combinations thereof. Therefore, the present invention provides a new type of battery additive material with high commercial application value in the field of batteries, which can be widely used in various types of batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The present invention is explained in detail through the following specific embodiments and drawings, so that those skilled in the art can better understand the present invention, but it should not be understood as limiting the scope of the present invention in any way.
[0034] Figure 1 A scanning electron microscope (SEM) photograph of a sodium supplement according to one embodiment of the present invention (Example 1) is shown.
[0035] Figure 2 The X-ray diffraction (XRD) pattern of the sodium supplement according to one embodiment of the present invention (Example 1) is shown.
[0036] Figure 3The XRD patterns of the sodium supplement according to one embodiment of the present invention (Example 1) before and after the air stability test (also known as the humidity test) are shown.
[0037] Figure 4 The electrochemical performance of a sodium supplement half-cell according to one embodiment of the present invention (Example 1) is shown.
[0038] Figure 5 The XRD patterns of the sodium supplementing agents according to various embodiments (Examples 2-5) of the present invention are shown.
[0039] Figure 6 A scanning electron microscope-X-ray energy dispersive spectrometer (SEM-EDS) photograph of a sodium supplement according to one embodiment of the present invention (Example 2) is shown.
[0040] Figure 7 The first cycle charge and discharge curves of the battery according to an embodiment of the present invention (Example 7) and a comparative embodiment (Comparative Example 2) are shown. DETAILED DESCRIPTION
[0041] In the context of describing the present invention (especially in the context of the claims), unless otherwise specified herein or clearly contradictory to the context, the terms "one / a kind" and "the / said" and similar uses should be interpreted as covering the singular and plural. Unless otherwise specified, the terms "comprising", "having", "including" and "containing" should be interpreted as open terms (i.e., "including, but not limited to"), but also include "essentially consisting of..." and "consisting of..." Partially closed or closed terms. Unless otherwise specified, the term "and / or" means either or both. For example, "A and / or B" means only A, only B, or both A and B. Unless otherwise specified herein, the recording of numerical ranges herein is intended only to be used as a shorthand method for independently referring to each individual value falling within the range, and each individual value is incorporated into this specification as if it is independently recorded herein.
[0042] Unless otherwise specified herein or the context is clearly contradictory, all methods described herein can be performed in any suitable order. Unless otherwise stated, the use of any and all examples or exemplary language (e.g., "such as") provided herein is intended only to better illustrate the present invention, without limiting the scope of the present invention. Any language in this specification should not be interpreted as indicating that any unclaimed element is essential to the practice of the present invention.
[0043] Preferred embodiments of the present invention are described herein, including the best mode of implementing the present invention known to the inventor. After reading the description herein, changes in those preferred embodiments may become apparent to those of ordinary skill in the art. The inventors expect that skilled persons will be able to appropriately adopt such changes, and expect that the present invention can be implemented in a manner different from that specifically described herein. Therefore, the present invention includes all variations and equivalents of the subject matter recorded in the appended claims as permitted by applicable law. Moreover, unless otherwise specified herein or the context is clearly contradictory, the present invention encompasses any combination of all possible variations of the above elements.
[0044] Listed below are definitions of various terms used to describe the materials disclosed herein. These definitions apply to the terms as used throughout this specification and claims, except where otherwise limited in specific instances, where the terms are used either individually or as part of a larger group.
[0045] As used herein, the terms "optional", "optionally", and "optionally" include both selection and non-selection. For example, "optionally modified" includes both modification and non-modification.
[0046] Throughout this specification, reference to "an aspect," "an aspect," "an embodiment," "some embodiments," "an embodiment," "a specific embodiment," "a related embodiment," "an embodiment," "an additional embodiment," or "a further embodiment" or a combination thereof means that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present invention. Therefore, the appearances of the aforementioned phrases in various places throughout this specification do not necessarily all refer to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.
[0047] The first material, the second material, the coated material, the composite material, the positive electrode, the separator, and the electrochemical device of the present invention can be applied to a battery system / battery, such as a lithium ion and sodium ion battery system. In one aspect, the electrochemical device and / or the battery system of the present invention comprises a battery cell, which comprises a positive electrode and a negative electrode, and optionally further comprises a current collector, an electrolyte, and / or a separator. In this article, "battery system" can be used interchangeably with "battery".
[0048] The "first" or "second" in the "first material" or "second material" described herein is only for the convenience of expression and does not have any limitation or evaluation on the defined materials.
[0049] The term "cathode" as used herein refers to the electrode with higher electrical potential in a battery.
[0050] The term "anode" as used herein refers to the electrode with lower electrical potential in a battery.
[0051] The term "sodium supplementation" as used herein refers to the technology of replenishing a sodium source into a battery before the battery operates.
[0052] The term "prelithiation" used herein refers to the technology of replenishing lithium source into the battery before the battery is put into operation.
[0053] The terms "sodium replenishing additive" or "sodium replenishing agent" used herein can be used interchangeably to refer to a material that can provide a supplement for the irreversible sodium ion loss of a battery system, and generally has a higher irreversible capacity.
[0054] As used herein, the terms “prelithiation additive” and “lithium replenisher” are used interchangeably to refer to materials that can provide supplements for the irreversible lithium ion loss of a battery system, and generally have a higher irreversible capacity.
[0055] The term "long-period periodic table" used herein may also be referred to as the "long-form periodic table", which refers to the most commonly used periodic table, which has 7 horizontal rows and 18 vertical rows, wherein each horizontal row is called a period, and each vertical row is called a group. The 7 horizontal periods can be divided into short periods (1st, 2nd, 3rd periods), long periods (4th, 5th, 6th periods) and incomplete periods (7th period). The vertical rows can be named from left to right as Group 1 to Group 18 with Arabic numerals, or can be named as Group IA, Group IIA, Group IIIB, Group IVB, Group VB, Group VIB, Group VIIB, Group VIII (including three vertical columns), Group IB, Group IIB, Group IIIA, Group IVA, Group VA, Group VIA, Group VIIA and Group 0 with Roman numerals.
[0056] The term "stoichiometric ratio" as used herein refers to the ratio of the amounts of each substance participating in the reaction.
[0057] As used herein, unless otherwise indicated, variables represented by the same letters have the same meaning.
[0058] In some embodiments, the “material that can be used for the positive electrode of a battery” described in the present invention may refer to a “positive electrode material for a battery”, also known as a “positive electrode active material for a battery” or a “positive electrode active material” or a “positive electrode material”.
[0059] Specifically, the present invention provides a novel battery additive material, the chemical formula of which is A 14 Fe6O16 (The simplest molecular formula is A7Fe3O8), wherein A is one or more elements selected from the IA and IIA groups of the long-period periodic table, such as one or more selected from lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, strontium, and barium. This material has never been disclosed in the prior art. 14 Fe6O 16 Or A7Fe3O8 can be doped with different elements independently at the A, Fe, and O sites to derive doped active materials (such as positive electrode active materials), coated active materials (such as positive electrode active materials) can be derived through coating technology, and composite active materials (such as positive electrode active materials) can be derived through compounding with other materials. This material and its series of derivatives can be used as positive electrode active materials for batteries and have high commercial application value. The present invention also provides a method for preparing the material and / or its derivatives and the use of the material and / or its derivatives in positive electrode active materials, battery positive electrodes, battery cells or diaphragms, electrochemical devices, etc.
[0060] In some embodiments, the present invention provides a material having a structure of formula (I):
[0061] Na 7n-x L x Fe 3n-y M y O 8n-a-b R a Q b (I)
[0062] in:
[0063] n is an integer selected from 1 to 10,
[0064] 0≤x≤7n,
[0065] 0≤y<3n,
[0066] 0≤a<8n,
[0067] 0≤b<8n,
[0068] L is one or more elements selected from Group IA and IIA elements in the long-period periodic table,
[0069] M is one or more metal elements selected from Groups IA-VIA, IB-VIIB and VIII in the long-period periodic table,
[0070] R is one or more selected from the elements of Group VIIA in the long-period periodic table, and
[0071] Q is one or more selected from the elements of Group VIA in the long-period periodic table.
[0072] In formula (I), the atomic molar ratio of (Na + L):(Fe + M):(O + R + Q) is 7:3:8.
[0073] In some embodiments, n is an integer selected from any one of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, preferably, n is selected from 1, 2, and 3.
[0074] In some embodiments, x is a value within the range formed by any two of the following numbers as endpoints: 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, and 70. In some embodiments, x is 0. In some embodiments, x is 7n, where n is defined as above. In some embodiments, x is a non-integer, for example, x can be a decimal selected from, for example, 0.01, 0.05, 0.10, 10.11, 20.20, 30.30, 40.40, 50.50, 60.60, 69.69, and the range formed by any two of these numbers as endpoints. When x is neither 0 nor 7n, the material can be used not only as a sodium supplement for sodium-ion batteries but also as a supplement for the metal ion battery represented by L. For example, when x is within the range of 0 - 7n and not the endpoint values (i.e., 0 and 7n) and L is lithium (Li), the material can be used as a sodium supplement for sodium-ion batteries and also as a lithium supplement for lithium-ion batteries.
[0075] In some embodiments, y is a value within the range formed by any two of the following numbers as endpoints: 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, and 30. In some embodiments, y is 0. In some embodiments, 0 < y < 3n / 2, where n is defined as above. In some embodiments, y is a non-integer, for example, y can be a decimal selected from, for example, 0.01, 0.05, 0.10, 1.50, 5.11, 10.20, 15.30, 20.40, 25.50, 29.60, and the range formed by any two of these numbers as endpoints.
[0076] In some embodiments, a is a value selected from the range formed by any two of the following numbers as endpoints: 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 35, and 40. In some embodiments, a is 0. In some embodiments, 0 < a < 4n, where n is defined as above. In some embodiments, a is a non-integer. For example, a can be a decimal selected from, for example, 0.01, 0.05, 0.10, 1.50, 5.11, 10.20, 15.30, 20.40, 25.50, 30.60, 35.50, 39.60, and the range formed by any two of these numbers as endpoints.
[0077] In some embodiments, b is a value selected from the range formed by any two of the following numbers as endpoints: 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, 30, 35, and 40. In some embodiments, b is 0. In some embodiments, 0 < b < 4n, where n is defined as above. In some embodiments, b is a non-integer. For example, b can be a decimal selected from, for example, 0.01, 0.05, 0.10, 1.50, 5.11, 10.20, 15.30, 20.40, 25.50, 30.60, 35.50, 39.60, and the range formed by any two of these numbers as endpoints.
[0078] In some embodiments, L is one or more elements selected from Group IA and Group IIA of the long-period form of the periodic table and excluding Na, and is an element that can be used for doping or substituting Na at the Na site. Preferably, L is one or more elements selected from lithium, potassium, rubidium, cesium, magnesium, calcium, strontium, and barium. In some embodiments, L is one or more elements selected from lithium, potassium, magnesium, calcium, and barium. In some embodiments, L is lithium.
[0079] In some embodiments, M is selected from one or more of the metal elements in the IA-VIA group, the IB-VIIB group and the VIII group in the long period periodic table and the elements other than Fe, and is an element that can be used for doping at the Fe position. Specifically, M is selected from one or more of the metal elements in the IA, IIA, IIIA, IVA, VA, VIA, IB, IIB, IIIB, IVB, VB, VIB, VIIB and VIII groups in the long period periodic table. Preferably, M is selected from one or more of lithium, magnesium, aluminum, nickel, boron, scandium, titanium, vanadium, chromium, manganese, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, iridium and tin. In some embodiments, M is selected from one or more of titanium, vanadium, chromium, manganese, cobalt, nickel, copper and zinc. In some embodiments, M is titanium.
[0080] In some embodiments, R is selected from one or more of the elements of Group VIIA in the long period periodic table, and is an element that can be used for doping at the O position. Preferably, R is selected from one or more of fluorine, chlorine, bromine, and iodine. In some embodiments, R is selected from one or more of fluorine, chlorine, and bromine. In some embodiments, M is fluorine.
[0081] In some embodiments, Q is one or more elements selected from Group VIA of the long period periodic table and other than O, and is an element that can be used for doping at the O position. Preferably, Q is one or more selected from sulfur, selenium, and tellurium. In some embodiments, Q is one or more selected from sulfur and selenium. In some embodiments, Q is sulfur.
[0082] In some embodiments, the present invention provides a material having a structure of formula (I):
[0083] Na 7n-x L x Fe 3n-y M y O 8n-a-b R a Q b (I)
[0084] Wherein formula (I) satisfies one or more of the following conditions:
[0085] 1) n is selected from 1, 2 and 3;
[0086] 2) x is 0 or 7n;
[0087] 3)0≤y<3n / 2;
[0088] 4)0≤a<4n;
[0089] 5)0≤b<4n;
[0090] 6) M is one or more selected from lithium, magnesium, aluminum, nickel, boron, scandium, titanium, vanadium, chromium, manganese, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, iridium and tin;
[0091] 7) L is one or more selected from lithium, potassium, rubidium, cesium, magnesium, calcium, strontium, and barium;
[0092] 8) R is one or more selected from fluorine, chlorine, bromine, and iodine; and
[0093] 9) Q is one or more selected from sulfur, selenium and tellurium.
[0094] In some embodiments, the material of formula (I) is selected from Na 7n Fe 3n O 8n 、Na 7n Fe 3n-y Ti y O 8n 、Na 7n Fe 3n- y Mn y O 8n 、Na 7n Fe 3n-y Al y O 8n 、Na 7n Fe 3n-y Co y O 8n 、Na 7n Fe 3n-y Cu y O 8n 、Na 7n Fe 3n-y Zn y O 8n 、Na 7n Fe 3n-y Ru y O 8n 、Na 7n Fe 3n-y Y y O 8n 、Na 7n Fe 3n-y B y O 8n 、Na 7n Fe 3n-y Mg y O 8n 、Na 7n Fe 3n-y Zr y O 8n 、Na 7n Fe3n-y Ni y O 8n 、Na 7n Fe 3n O 8n-a F a One or more of, wherein n is 1 or 2, 0 <y<3n,0<a<8n。
[0095] In some embodiments, the material of formula (I) is Na7Fe3O8 or Na 14 Fe6O 16 .
[0096] In some embodiments, the present invention provides a method for preparing a material of formula (I) according to the present invention, the method comprising the following steps:
[0097] (a) mixing Fe2O3, Na2O and / or an oxide of L, and an optional dopant precursor to obtain a precursor mixture, wherein the stoichiometric ratio between Fe2O3 and the oxide of Na2O and / or L is 1:9-9:1, preferably 1:9-1:1, more preferably 1:6-1:2, wherein L is one or more elements selected from Groups IA and IIA of the long period periodic table;
[0098] (b) heating the precursor mixture at a temperature of 100-1200° C., preferably 200-800° C., for 1-200 hours, preferably 20-100 hours under an inert atmosphere for high temperature sintering;
[0099] (c) After cooling, the material is obtained.
[0100] In some embodiments, the stoichiometric ratio between Fe2O3 and Na2O and / or L oxide is in a range consisting of any two of the following ratios as endpoints: 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, and 9:1.
[0101] In some embodiments, the inert atmosphere is at least one selected from nitrogen, argon, and helium.
[0102] In some embodiments, the precursor mixture is subjected to high temperature sintering at a temperature within a range consisting of any two of the following values as endpoints: 100° C., 200° C., 300° C., 400° C., 500° C., 600° C., 700° C., 800° C., 900° C., 1000° C., 1100° C., and 1200° C. The time of high temperature sintering can be within a range consisting of any two of the following values as endpoints: 1 hour, 3 hours, 5 hours, 8 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 40 hours, 50 hours, 60 hours, 70 hours, 80 hours, 90 hours, 100 hours, 110 hours, 120 hours, 130 hours, 140 hours, 150 hours, 160 hours, 170 hours, 180 hours, 190 hours, and 200 hours.
[0103] In some embodiments, the dopant precursor is one or more selected from the oxide of M, sodium fluoride, sodium sulfide, iron fluoride and iron sulfide, wherein M is one or more selected from the metal elements in the IA-VIA group, the IB-VIIB group and the VIII group in the long period periodic table; preferably, the dopant precursor is an oxide of M, wherein M is one or more selected from the metal elements in the IA, IIA, IIIA, IVA, VA, VIA, IB, IIB, IIIB, IVB, VB, VIB, VIIB and VIII groups in the long period periodic table. M is an element doped at the Fe position, which is an element other than Fe. Preferably, M is one or more selected from lithium, magnesium, aluminum, nickel, boron, scandium, titanium, vanadium, chromium, manganese, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, iridium and tin. In some embodiments, M is one or more selected from titanium, vanadium, chromium, manganese, cobalt, nickel, copper and zinc. In some embodiments, M is titanium.
[0104] In some embodiments, the present invention provides a coated material comprising a core and a coating layer covering the surface of the core, wherein:
[0105] The core comprises a material of formula (I) according to the present invention;
[0106] The coating layer comprises one or more materials selected from the group consisting of metal fluorides, metal carbides, metal oxides, polymers, carbon, and combinations thereof.
[0107] In the present invention, there may or may not be a cavity between the coating layer and the core, and the coating layer may be a continuous layer or a discontinuous layer. The material of the coating layer includes but is not limited to: metal fluoride, metal carbide, metal oxide, polymer.
[0108] In some embodiments, the coating layer comprises one or more of a metal fluoride coating layer, a metal carbide coating layer, and a metal oxide coating layer, wherein the metal elements in the metal fluoride, the metal carbide, and the metal oxide are independently selected from one or more of nickel, cobalt, aluminum, manganese, lithium, potassium, barium, iron, calcium, copper, zinc, titanium, magnesium, zirconium, strontium, chromium, tin, antimony, tungsten, niobium, molybdenum, vanadium, palladium, bismuth, cesium, hafnium, tantalum, polonium, gallium, indium, thallium, yttrium, scandium, lanthanide elements, and combinations thereof.
[0109] In some embodiments, the coating comprises a metal fluoride coating, wherein the metal fluoride comprises metal fluorides of nickel, cobalt, aluminum, manganese, lithium, potassium, barium, iron, calcium, copper, zinc, titanium, magnesium, zirconium, strontium, chromium, tin, antimony, tungsten, niobium, molybdenum, vanadium, palladium, bismuth, cesium, hafnium, tantalum, polonium, gallium, indium, thallium, yttrium, scandium and lanthanide elements.
[0110] In some embodiments, the coating comprises a metal carbide coating, wherein the metal carbide comprises metal carbides of nickel, cobalt, aluminum, manganese, lithium, potassium, barium, iron, calcium, copper, zinc, titanium, magnesium, zirconium, strontium, chromium, tin, antimony, tungsten, niobium, molybdenum, vanadium, palladium, bismuth, cesium, hafnium, tantalum, polonium, gallium, indium, thallium, yttrium, scandium, and lanthanide elements.
[0111] In some embodiments, the coating layer comprises a metal oxide coating layer, wherein the metal oxide is selected from nickel, cobalt, aluminum, manganese, lithium, potassium, barium, iron, calcium, copper, zinc, titanium, magnesium, zirconium, strontium, chromium, tin, antimony, tungsten, niobium, molybdenum, vanadium, palladium, bismuth, cesium, hafnium, tantalum, polonium, gallium, indium, thallium, yttrium, scandium and metal oxides of lanthanide elements. Preferably, the metal element in the metal oxide is selected from nickel, cobalt, aluminum, manganese, lithium, potassium, barium, iron, calcium, copper, zinc, titanium, magnesium, zirconium and combinations thereof. More preferably, in some embodiments, the metal oxide is aluminum oxide.
[0112] In some embodiments, the coating layer comprises a polymer coating layer, a carbon coating layer and a combination thereof, wherein the polymer includes one or more selected from the following: polypyrrole polymers and modified products thereof, polythiophene polymers and modified products thereof, polyamide polymers and modified products thereof, polyethylene oxide polymers and modified products thereof, polyvinylidene fluoride polymers and modified products thereof, polyacrylate polymers and modified products thereof, polyacrylonitrile polymers and modified products thereof, polyether polymers and modified products thereof, polysiloxane polymers and modified products thereof or polyanion single ion conductor type polymers and combinations thereof. One or more.
[0113] The preparation method of the coated material according to the present invention is not subject to any restriction, and suitable coating method can be selected by those skilled in the art according to the material used. For example, coating can be carried out by one or more methods in vacuum evaporation, ion plating, chemical vapor deposition (CVD) (such as thermal CVD, plasma CVD, organometallic CVD, metal CVD, etc.), atomic layer deposition (ALD), radio frequency sputtering, magnetron sputtering, reactive sputtering, ball milling mixing, sol-gel method, hydrothermal or solvent thermal coating, spray drying.
[0114] In some embodiments, the coated material according to the present invention can be obtained by mixing Fe2O3, Na2O and / or L oxides, a coating layer precursor material and an optional dopant precursor and heating at a certain temperature (e.g., 100-800°C) for a certain time (e.g., 1-12 hours) to perform high-temperature sintering (preferably high-temperature sintering under an inert atmosphere), followed by cooling.
[0115] In some embodiments, the coated material according to the present invention can be obtained by first forming a core material, then mixing the core material with a coating layer precursor material and heating at a certain temperature (e.g., 100-800°C) for a certain time (e.g., 1-12 hours) to perform high-temperature sintering (preferably high-temperature sintering under an inert atmosphere), and then cooling.
[0116] In some embodiments, the present invention provides a composite material comprising a first material and a second material, wherein the first material comprises a material of formula (I) according to the present invention; and the second material is a battery active material different from the first material.
[0117] In some embodiments, the second material is at least one sodium-containing positive electrode active material selected from Prussian blue, polyanionic compounds, transition metal layered oxides, and sodium-containing organic compounds. Preferably, the second material is selected from Na(Ni x’ Fe y’ Mn 1-x’-y’ )O2、Na 0.74 (Ni x’ Fe y’ Mn 1-x’-y’ )O2、Na 0.67 (Ni x’ Mn y’ Ti 1-x’-y’ )O2、Na 0.67 (Ni x’ Mn y’ Zn z’ Cu 1-x’-y’-z’)O2, Na2M’[Fe(CN)6], NaVPO4F, Na2FePO4F, Na3V2(PO4)3, Na2Fe2(SO4)3, NaTiO2, NaMnO2, NaFeO2, NaCoO2, NaNiO2, Na2C6O6, and combinations thereof, where 0 < x’ < 1, 0 < y’ < 1, 0 < z’ < 1, and M’ is selected from Fe, Co, Mn, Ni, Cu, and combinations thereof.
[0118] In some embodiments, the second material is selected from Na(Ni x’ Fe y’ Mn 1-x’-y’ )O2, Na 0.74 (Ni x’ Fe y’ Mn 1-x’-y’ )O2, Na 0.67 (Ni x’ Mn y’ Ti 1-x’-y’ )O2, Na 0.67 (Ni x’ Mn y’ Zn z’ Cu 1-x’-y’-z’ )O2, and combinations thereof, where in each chemical formula, x’, y’, and z’ are each independently selected from values (including or not including the endpoints) within the range formed by any two of the following numbers: 0, 1 / 50, 1 / 30, 1 / 20, 1 / 10, 1 / 9, 1 / 8, 1 / 7, 1 / 6, 1 / 5, 1 / 4, 1 / 3, 1 / 2, and 1.
[0119] In some embodiments, the second material is selected from NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, Na 0.74 Ni 1 / 4 Fe 1 / 4 Mn 1 / 2 O2, and combinations thereof.
[0120] In some embodiments, the second material is selected from Na2M’[Fe(CN)6], where M’ is selected from Co, Mn, Ni, Cu, and combinations thereof.
[0121] In some embodiments, the second material is one or more selected from ternary materials (such as nickel cobalt manganese, nickel cobalt aluminum, and / or nickel cobalt lithium ternary materials), sodium vanadium phosphate, sodium fluorovanadate, sodium cobaltate, sodium manganate, and combinations thereof. As used herein, the term "ternary material" refers to any known ternary material in the battery field.
[0122] In some embodiments, the weight ratio of the first material to the second material is 1:30 to 30: 1. The weight ratio of the first material to the second material can be in a range consisting of any two of the following ratios as endpoints: 1:30, 1:29, 1:28, 1:27, 1:26, 1:25, 1:24, 1:23, 1:22, 1:21, 1:20, 1:18, 1:15, 1:13, 1:10, 1:8, 1:5, 1:2, 1:1, 2:1, 5:1, 8:1, 10:1, 13:1, 15:1, 18:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1.
[0123] The composite method of the first material and the second material is not limited in any way and can be selected by those skilled in the art as needed. In some embodiments, the composite method of the first material and the second material can be a simple physical mixture or a form in which the second material is attached to the outside of the first material.
[0124] In some embodiments, the first material further comprises one or more additional materials selected from the following: NaN3, Na2O, Na2O2, Na2C2O4, Na2CO3, Na3C6H5O7, Na2C2O2N2, Na2C2N4, Na2C4H5NO4, Na3C7H8NO6 and combinations thereof. The additional materials can be combined with the material of formula (I) by mixing or any other means to serve as the first material.
[0125] In some embodiments, the weight ratio of the material of formula (I) to the additional material is 1:30 to 30: 1. The weight ratio of the material of formula (I) to the additional material can be in a range consisting of any two of the following ratios as endpoints: 1:30, 1:29, 1:28, 1:27, 1:26, 1:25, 1:24, 1:23, 1:22, 1:21, 1:20, 1:18, 1:15, 1:13, 1:10, 1:8, 1:5, 1:2, 1:1, 2:1, 5:1, 8:1, 10:1, 13:1, 15:1, 18:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1.
[0126] When the material of formula (I) is compounded with the second material and / or the above-mentioned additional material for charging and discharging, the material of formula (I) as a transition metal compound can also play a catalytic role when compounded with the second material and / or the above-mentioned additional material. The material of formula (I) and the second material and / or the above-mentioned additional material are compounded as different types of sodium supplements, which can play the role of sodium supplementation at the same time, and on the other hand, the material of formula (I) can help other sodium supplements reduce the decomposition voltage, thereby obtaining a higher sodium supplement capacity.
[0127] In some embodiments, the present invention provides a method for preparing a composite material according to the present invention, the method comprising the step of compounding a first material and a second material in a mixed and / or coated form. The mixing preferably comprises the step of mixing the first material and the second material by stirring and / or grinding. The coating preferably comprises the step of attaching the second material to the outside of the first material.
[0128] In some embodiments, the present invention provides a positive electrode active material comprising one or more of the material of formula (I) according to the present invention, the coated material according to the present invention, the composite material according to the present invention, and combinations thereof.
[0129] In some embodiments, the present invention provides a positive electrode for a battery, comprising a positive electrode active material according to the present invention, an optional conductive agent, and an optional binder.
[0130] The selection of the conductive agent is not subject to any restriction and can be selected by those skilled in the art as needed. In some embodiments, the conductive agent is selected from at least one of carbon black, acetylene black, Ketjen black, conductive graphite, carbon fiber, carbon nanotubes (CNTs), graphene, graphene oxide, reduced graphene oxide and combinations thereof. Preferably, in some embodiments, the conductive agent is a carbon nanotube (CNTs) conductive agent.
[0131] Generally speaking, the amount of the conductive agent is 0.5-10% by weight based on the total weight of the positive electrode of the battery. Further, the amount of the conductive agent can be within a range consisting of any two of the following values as endpoints based on the total weight of the positive electrode of the battery: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%.
[0132] The selection of binding agent is not subject to any restriction, and can be selected as needed by those skilled in the art. In some embodiments, the binding agent is selected from at least one of polyvinylidene fluoride (PVDF), polyvinylidene chloride, polytetrafluoroethylene, polyethylene oxide, polyvinylidene chloride-hexafluoropropylene, polyacrylic acid, polyacrylonitrile, polyacrylamide, polyamide, polyamide-imide, polymethyl methacrylate, polycarbonate, carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene-butadiene copolymer, sodium alginate, styrene-butadiene rubber and combinations thereof. Preferably, in some embodiments, the binding agent is PVDF.
[0133] Generally speaking, the amount of the binder is 0.5-10% by weight based on the total weight of the positive electrode of the battery. Further, the amount of the binder can be within a range consisting of any two of the following values as endpoints based on the total weight of the positive electrode of the battery: 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%.
[0134] In some embodiments, the weight ratio of the positive electrode active material, the binder and the conductive agent is 1-10: 1: 1 or 2-9: 1: 1 or 3-8: 1: 1 or 4-7: 1: 1 or 5-6: 1: 1. For example, in some embodiments, the weight ratio of the positive electrode active material, the binder and the conductive agent is 8: 1: 1.
[0135] In some embodiments, the present invention provides an electrode sheet, which comprises one or more of the material of formula (I) according to the present invention, the coated material according to the present invention, the composite material according to the present invention, and a combination thereof. Preferably, in some embodiments, the electrode sheet comprises a coating and the coating comprises one or more of the material of formula (I) according to the present invention, the coated material according to the present invention, the composite material according to the present invention, and a combination thereof.
[0136] In the field of electrochemistry, electrode sheets are important components in electrochemical cells and other electrochemical devices. In the present invention, electrode sheets refer to electrode sheets used in metal ion batteries, for example, positive electrode sheets (also known as "positive electrode sheets") and negative electrode sheets (also known as "negative electrode sheets"). In some embodiments, the electrode sheets according to the present invention further include a conductive substance. The conductive substance may be selected from conductive metals, conductive polymers, and combinations thereof. In some embodiments, the electrode sheets according to the present invention further include a current collector. The current collector may be made of a metal grid, conductive paper, or a combination thereof.
[0137] In some embodiments, the present invention provides a diaphragm, which comprises one or more of the material of formula (I) according to the present invention, the coated material according to the present invention, the composite material according to the present invention, and a combination thereof. Preferably, in some embodiments, the diaphragm comprises a coating and the coating comprises one or more of the material of formula (I) according to the present invention, the coated material according to the present invention, the composite material according to the present invention, and a combination thereof.
[0138] In this article, the term "separator" refers to a separator used in a battery, also known as a "battery separator". In some embodiments, a battery separator refers to a separator material located between the positive electrode and the negative electrode of a battery, and its main function is to isolate the positive and negative electrodes and prevent the electrons in the battery from passing freely, and allow the ions in the electrolyte to pass freely between the positive and negative electrodes. In some embodiments, the separator according to the present invention further comprises a polymer material. The polymer material can be selected from polyethylene, polypropylene and a combination thereof.
[0139] In some embodiments, the present invention provides an electrochemical device, comprising at least one of a positive electrode active material according to the present invention, a battery positive electrode according to the present invention, an electrode sheet or a separator according to the present invention, and a combination thereof. Preferably, in some embodiments, the electrochemical device is an energy storage system, such as a battery, more specifically a sodium ion battery, a lithium ion battery, a potassium ion battery, a rubidium ion battery, a cesium ion battery, a magnesium ion battery, a calcium ion battery, a strontium ion battery, a barium ion battery, or a combination thereof, especially a sodium ion battery, a lithium ion battery, or a combination thereof.
[0140] Therefore, the present invention can be applied to lithium-ion and sodium-ion battery systems, which are also the most mature energy storage systems for commercial applications. Its core components include positive electrode, negative electrode, electrolyte and diaphragm. During the charging process, under the action of the external circuit, lithium / sodium ions are deintercalated from the positive electrode active material and embedded into the negative electrode through the electrolyte diaphragm. At the same time, the positive electrode loses electrons and flows out from the external circuit through the current collector; the discharge process is the opposite, lithium / sodium ions are deintercalated from the negative electrode back to the positive electrode, and electrons move from the negative electrode to the positive electrode through the external circuit and do work externally.
[0141] Example
[0142] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0143] The experimental techniques and methods used in the present example are all conventional technical methods unless otherwise specified. The materials, reagents, etc. used in the examples can be synthesized by known methods or obtained through commercial channels unless otherwise specified. The synthetic techniques and conditions used are also easily understood by those skilled in the art.
[0144] Suitable modifications and adaptations of the various conditions, formulations, and other parameters normally encountered in the art and which are apparent to those skilled in the art in light of this disclosure are within the spirit and scope of the present invention.
[0145] Example 1 Sodium ion battery using positive electrode sodium supplement
[0146] 1) Preparation of positive electrode sodium supplement:
[0147] Fe2O3 and Na2O were weighed in a stoichiometric ratio of 1:5, the weighed powders were mixed and placed in a tube furnace, dry argon was continuously introduced at a flow rate of 60 sccm, and heated at 600°C for 200 hours. After sintering, the product was ground and sieved to obtain the positive electrode sodium supplement Na7Fe3O8.
[0148] The SEM picture of the material is shown in Figure 1 As shown in Figure 2, the overall morphology of the material is blocky and evenly distributed. Figure 2 The synthesized material is consistent with the target material, has good crystallinity, and has no obvious impurity peaks.
[0149] The material was subjected to an air stability test (also known as a humidity test): a portion of the product powder was taken out and placed in a pharmaceutical tube and sealed with a sealing film, and then transferred to a constant temperature and humidity moisture-proof box with a humidity of 26% and a temperature of 25°C. After being stored for 24 hours, it was taken out and the appearance of the material was observed and an XRD test was performed.
[0150] The results of the air stability test showed that the material had no obvious color and morphology changes. XRD characterization was performed on the material before and after the air stability test. The results are as follows Figure 3 As shown, there is no obvious change in the material phase.
[0151] 2) Preparation of battery positive electrode:
[0152] Take the Na7Fe3O8 prepared in step 1) as the positive electrode active material, and weigh the positive electrode active material, binder PVDF and carbon nanotube (CNTs) conductive agent according to a weight ratio of 8:1:1. First dissolve PVDF in NMP, then add CNTs and disperse evenly, and finally add the above positive electrode active material. After uniform dispersion, the obtained positive electrode slurry is filtered and coated on the aluminum foil current collector, and then dried, rolled and die-cut to obtain a circular positive electrode sheet with a diameter of 13mm and a loading of about 1.5mg / cm 2 .
[0153] 3) Assemble the battery:
[0154] Match the positive electrode sheet prepared in step 2) with the sodium sheet (specifications are 14mm in diameter and 0.45mm in thickness, the same below), and assemble a half-cell with 1MNaClO4+EC / PC (1:1, v / v) (i.e., sodium perchlorate as electrolyte, propylene carbonate and ethylene carbonate mixed in a volume ratio of 1:1 as solvent, the same below) as electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed on the channel of the Land constant current charge and discharge test equipment (model Land CT2001A) at a rate of 0.05C (the current value of the rated capacity discharged in 1 hour is taken as 1C, 1C=411mAh / g, the same below), and the voltage range was 2.0V-4.5V. The first cycle charge and discharge curve is shown in the figure. Figure 4 shown.
[0155] This material can release a specific capacity of 251.1 mAh / g when charged to 4.2V in the first cycle, 280.0 mAh / g at 4.3V, and 350.7 mAh / g at 4.5V, but has almost no capacity when discharged to 2.0V in the first cycle.
[0156] Example 2 Sodium ion battery using doped positive electrode sodium supplement
[0157] 1) Preparation of positive electrode sodium supplement:
[0158] Fe2O3, Na2O, TiO2, and Al2O3 were weighed and mixed thoroughly according to the stoichiometric ratio of 0.88:5:0.02:0.1. The mixed powder was placed in a tube furnace, and dry argon was continuously introduced at a flow rate of 60 sccm. It was heated at 600°C for 200 hours. After sintering, the product was ground and sieved to obtain a positive electrode sodium supplement doped with aluminum and titanium elements. The XRD test results of the product are shown in Figure 5 It can be seen that the material phase has no obvious difference compared with Na7Fe3O8, and no impurity peaks appear, indicating the successful incorporation of TiO2 and Al2O3. The SEM-EDS photo of the product powder is shown in Figure 6As shown, it can be seen that there are obvious Fe and Al elements in the material, which further illustrates the successful incorporation of Fe and Al elements. The elemental analysis results obtained by EDS test are shown in Table 1. The molecular formula of the product can be deduced from the atomic percentage of transition metal elements to be Na7Fe 2.622 Al 0.304 Ti 0.055 □ 0.019 O8, where □ represents a vacancy.
[0159] Table 1 EDS element analysis results
[0160] element Weight Percent Atomic Percent C 5.26 9.63 O 37.29 51.29 Na 26.43 25.30 Al 3.64 2.97 Ti 0.39 0.18 Fe 27.00 10.64 Total 100.00 100.00
[0161] 2) Preparation of battery positive electrode:
[0162] Take the material prepared in step 1) as the positive electrode active material, and weigh the positive electrode active material, binder PVDF and carbon nanotube (CNTs) conductive agent according to a weight ratio of 8:1:1. First, dissolve PVDF in N-methylpyrrolidone (NMP), then add CNTs and disperse them evenly, and finally add the above positive electrode active material. After uniform dispersion, the obtained positive electrode slurry is filtered and coated on the aluminum foil current collector, and then dried, rolled and die-cut to obtain a circular positive electrode sheet with a diameter of 13mm and a loading of about 1.5mg / cm 2 .
[0163] 3) Assemble the battery:
[0164] The positive electrode sheet prepared in step 2) was matched with the sodium sheet, and a half-cell was assembled using 1M NaClO4+EC / PC (1:1, v / v) as the electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed in the voltage range of 2.5-4.5V according to the same procedure as in Example 1.
[0165] The material can release a specific capacity of 379.4 mAh / g when charged to 4.5 V in the first cycle, but has almost no capacity when discharged to 2.0 V in the first cycle.
[0166] Example 3 Sodium ion battery using doped positive electrode sodium supplement
[0167] 1) Preparation of positive electrode sodium supplement:
[0168] Fe2O3, Na2O, and NaF were weighed and mixed according to the stoichiometric ratio of 1:4.75:0.25, and the mixed powder was placed in a tube furnace, and dry argon was continuously introduced at a flow rate of 60 sccm, and heated at 600°C for 200 hours. After sintering, the product was ground and sieved to obtain the fluorine-doped positive electrode sodium supplement Na7Fe3O 7.6 F 0.4The XRD test results of the powder are shown in Figure 5 .
[0169] 2) Preparation of battery positive electrode:
[0170] Take the material prepared in step 1) as the positive electrode active material, and weigh the positive electrode active material, binder PVDF and carbon nanotube (CNTs) conductive agent according to a weight ratio of 8:1:1. First dissolve PVDF in NMP, then add CNTs to disperse evenly, and finally add the above positive electrode active material. After uniform dispersion, the obtained positive electrode slurry is filtered and coated on the aluminum foil current collector, and then dried, rolled and die-cut to obtain a circular positive electrode sheet with a diameter of 13mm and a loading of about 1.5mg / cm 2 .
[0171] 3) Assemble the battery:
[0172] The positive electrode sheet prepared in step 2) was matched with the sodium sheet, and a half-cell was assembled using 1M NaClO4+EC / PC (1:1, v / v) as the electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed in the voltage range of 2.5-4.5V according to the same procedure as in Example 1.
[0173] The material can release a specific capacity of 394.1 mAh / g when charged to 4.5 V in the first cycle, but has almost no capacity when discharged to 2.0 V in the first cycle. The incorporation of transition metal elements improves the kinetic properties of the material and reduces the decomposition voltage of the material, so that the doped product can release a higher specific capacity.
[0174] Example 4 Sodium ion battery using coated positive electrode sodium supplement
[0175] 1) Preparation of positive electrode sodium supplement:
[0176] Fe2O3 and Na2O were weighed in a stoichiometric ratio of 1:5, the weighed powders were mixed and placed in a tubular furnace, dry argon was continuously introduced at a flow rate of 60 sccm, and heated at 600°C for 200 hours. After sintering was completed and cooled to room temperature, the obtained powder was ground and sieved to obtain the positive electrode sodium supplement Na7Fe3O8. The obtained material was fully mixed with 20% by weight of glucose and placed in a tubular furnace, dry argon was continuously introduced at a flow rate of 60 sccm, and heated at 350°C for 4 hours. After sintering was completed and cooled to room temperature, the obtained product was ground and sieved to obtain the carbon-coated positive electrode sodium supplement Na7Fe3O8. The XRD test results of the powder are shown in Figure 5 .
[0177] 2) Preparation of battery positive electrode:
[0178] Take the material prepared in step 1) as the positive electrode active material, and weigh the positive electrode active material, binder PVDF and carbon nanotube (CNTs) conductive agent according to a weight ratio of 8:1:1. First dissolve PVDF in NMP, then add CNTs to disperse evenly, and finally add the above positive electrode active material. After uniform dispersion, the obtained positive electrode slurry is filtered and coated on the aluminum foil current collector, and then dried, rolled and die-cut to obtain a circular positive electrode sheet with a diameter of 13mm and a loading of about 1.5mg / cm 2 .
[0179] 3) Assemble the battery:
[0180] The positive electrode sheet prepared in step 2) was matched with the sodium sheet, and a half-cell was assembled using 1M NaClO4+EC / PC (1:1, v / v) as the electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed in the voltage range of 2.0-4.5V according to the same procedure as in Example 1.
[0181] The material can release a specific capacity of 370.4 mAh / g when charged to 4.5 V in the first cycle, but has almost no capacity when discharged to 2.0 V in the first cycle. After the material is coated, the air stability is improved, the deactivated part is reduced, and the corresponding specific capacity is improved.
[0182] Example 5 Sodium ion battery using coated positive electrode sodium supplement
[0183] 1) Preparation of positive electrode sodium supplement:
[0184] Fe2O3 and Na2O were weighed in a stoichiometric ratio of 1:5, the weighed powders were mixed and placed in a tube furnace, dry argon was continuously introduced at a flow rate of 60 sccm, and heated at 600°C for 200 hours. After sintering, the powder was cooled to room temperature, and then ground and sieved to obtain the positive electrode sodium supplement Na7Fe3O8. The obtained material was fully mixed with 10% by weight of aluminum isopropoxide, and the mixed powder was placed in a tube furnace, dry argon was continuously introduced at a flow rate of 60 sccm, and heated at 250°C for 2 hours. After sintering, the product was cooled to room temperature, and then ground and sieved to obtain the positive electrode sodium supplement Na7Fe3O8 coated with alumina. The XRD test results of the powder are shown in Figure 5 .
[0185] 2) Preparation of battery positive electrode:
[0186] Take the material prepared in step 1) as the positive electrode active material, and weigh the positive electrode active material, binder PVDF and carbon nanotube (CNTs) conductive agent according to a weight ratio of 8:1:1. First dissolve PVDF in NMP, then add CNTs to disperse evenly, and finally add the above positive electrode active material. After uniform dispersion, the obtained positive electrode slurry is filtered and coated on the aluminum foil current collector, and then dried, rolled and die-cut to obtain a circular positive electrode sheet with a diameter of 13mm and a loading of about 1.5mg / cm 2 .
[0187] 3) Assemble the battery:
[0188] The positive electrode sheet prepared in step 2) was matched with the sodium sheet, and a half-cell was assembled using 1M NaClO4+EC / PC (1:1, v / v) as the electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed in the voltage range of 2.0-4.5V according to the same procedure as in Example 1.
[0189] The material can release a specific capacity of 375.6 mAh / g when charged to 4.5 V in the first cycle, but has almost no capacity when discharged to 2.0 V in the first cycle. After the material is coated, the air stability is improved, the deactivated part is reduced, and the corresponding specific capacity is improved.
[0190] Example 6 Sodium ion battery using a composite positive electrode sodium supplement
[0191] 1) Preparation of positive electrode sodium supplement:
[0192] Fe2O3 and Na2O were weighed in a stoichiometric ratio of 1:5, the weighed powders were mixed and placed in a tube furnace, dry argon was continuously introduced at a flow rate of 60 sccm, and heated at 600°C for 200 hours. After sintering, the product was ground and sieved to obtain the positive electrode sodium supplement Na7Fe3O8.
[0193] 2) Preparation of battery positive electrode:
[0194] The material prepared in step 1) is used as a sodium supplement additive, and the sodium supplement additives NaNi and 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, Na7Fe3O8, binder PVDF and carbon nanotubes (CNTs) conductive agent. First, PVDF was dissolved in NMP, then CNTs were added and dispersed evenly, and finally the above-mentioned sodium supplement additives Na7Fe3O8 and NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3After being evenly dispersed, the obtained positive electrode slurry was filtered and coated on the aluminum foil current collector, and then dried, rolled and die-cut to obtain a composite positive electrode sodium supplementation electrode sheet, that is, a circular positive electrode sheet with a diameter of 13 mm and a loading of about 7.5 mg / cm 2 .
[0195] 3) Assemble the battery:
[0196] The positive electrode sheet prepared in step 2) was matched with the sodium sheet, and a half-cell was assembled using 1M NaClO4+EC / PC (1:1, v / v) as the electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed in the voltage range of 2.0-4.2V according to the same procedure as in Example 1.
[0197] The material can release a specific capacity of 192.6mAh / g when charged to 4.2V in the first cycle, while the original positive electrode material's first cycle charging capacity is about 175mAh / g, indicating that part of it is provided by the sodium supplement; when discharged to 2.0V, the specific capacity is 165.0mAh / g, and the positive electrode active material's own capacity release is not negatively affected. The final battery's first cycle coulomb efficiency is 85.80%, while the original positive electrode material's first cycle coulomb efficiency is about 93%, and the difference shows that the sodium supplement effect is obvious.
[0198] Example 7 Sodium ion battery using a composite positive electrode sodium supplement
[0199] 1) Preparation of positive electrode sodium supplement:
[0200] Fe2O3 and Na2O were weighed in a stoichiometric ratio of 1:5, the weighed powders were mixed and placed in a tube furnace, dry argon was continuously introduced at a flow rate of 60 sccm, and heated at 600°C for 200 hours. After sintering, the product was ground and sieved to obtain the positive electrode sodium supplement Na7Fe3O8.
[0201] 2) Preparation of battery positive electrode:
[0202] The material prepared in step 1) is used as a sodium supplement additive, and the sodium supplement additive Na and 0.74 Ni 1 / 4 Fe 1 / 4 Mn 1 / 2 O2, Na7Fe3O8, binder PVDF and carbon nanotubes (CNTs) conductive agent. First, PVDF was dissolved in NMP, then CNTs were added and dispersed evenly, and finally the above sodium supplement additives Na7Fe3O8 and Na 0.74 Ni 1 / 4 Fe 1 / 4 Mn 1 / 2O2. After being evenly dispersed, the obtained positive electrode slurry was filtered and coated on the aluminum foil current collector, and then dried, rolled and die-cut to obtain a composite positive electrode sodium supplementation electrode sheet, that is, a circular positive electrode sheet with a diameter of 13mm and a loading of about 7.5mg / cm 2 .
[0203] 3) Assemble the battery:
[0204] The positive electrode sheet prepared in step 2) was matched with the sodium sheet, and a half-cell was assembled with 1M NaClO4+EC / PC (1:1, v / v) as the electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed in the voltage range of 2.0-4.3V according to the same procedure as in Example 1. The first cycle charge and discharge curve is as follows: Figure 6 as shown in .
[0205] The material can release a specific capacity of 188.2mAh / g when charged to 4.3V in the first cycle, while the original positive electrode material's first cycle charging capacity is about 165mAh / g, indicating that part of it is provided by the sodium supplement; when discharged to 2.0V, the specific capacity is 155.5mAh / g, and the positive electrode active material's own capacity release is not negatively affected. The final battery's first cycle coulomb efficiency is 82.33%, while the original positive electrode material's first cycle coulomb efficiency is about 92%, and the difference shows that the sodium supplement effect is obvious.
[0206] Comparative Example 1: Sodium ion battery without using the sodium supplement agent of the present invention to supplement sodium
[0207] 1) Preparation of battery positive electrode:
[0208] NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was used as the positive electrode active material, and the positive electrode active material, binder PVDF, and carbon nanotube (CNTs) conductive agent were weighed according to a weight ratio of 8:1:1. PVDF was first dissolved in NMP, then CNTs were added and dispersed evenly, and finally the above positive electrode active materials were added. After uniform dispersion, the obtained positive electrode slurry was filtered and coated on the aluminum foil current collector, and then dried, rolled, and die-cut to obtain a circular positive electrode sheet with a diameter of 13 mm, with a loading of about 7.5 mg / cm 2 .
[0209] 2) Assemble the battery:
[0210] The positive electrode sheet prepared in step 1) was matched with the sodium sheet, and a half-cell was assembled using 1M NaClO4+EC / PC (1:1, v / v) as the electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed in the voltage range of 2.0-4.2V according to the same procedure as in Example 1.
[0211] The material can release a specific capacity of 174.6 mAh / g when charged to 4.2 V in the first cycle, and a specific capacity of 162.2 mAh / g when discharged to 2.0 V, with a first-cycle coulombic efficiency of 92.89%.
[0212] Comparative Example 2: Sodium ion battery without sodium supplementation using the sodium supplement agent of the present invention
[0213] 1) Preparation of battery positive electrode:
[0214] Will Na 0.74 Ni 1 / 4 Fe 1 / 4 Mn 1 / 2 O2 was used as the positive electrode active material, and the positive electrode active material, binder PVDF, and carbon nanotube (CNTs) conductive agent were weighed according to a weight ratio of 8:1:1. PVDF was first dissolved in NMP, then CNTs were added and dispersed evenly, and finally the above positive electrode active materials were added. After uniform dispersion, the obtained positive electrode slurry was filtered and coated on the aluminum foil current collector, and then dried, rolled, and die-cut to obtain a circular positive electrode sheet with a diameter of 13 mm, with a loading of about 7.5 mg / cm 2 .
[0215] 2) Assemble the battery:
[0216] The positive electrode sheet prepared in step 1) was matched with the sodium sheet, and a half-cell was assembled with 1M NaClO4+EC / PC (1:1, v / v) as the electrolyte. After the battery was left to stand for 24 hours, an electrochemical test was performed in the voltage range of 2.0-4.3V according to the same procedure as in Example 1. The first cycle charge and discharge curve is as follows: Figure 6 as shown in .
[0217] The material can release a specific capacity of 166.2 mAh / g when charged to 4.3 V in the first cycle, and a specific capacity of 153.1 mAh / g when discharged to 2.0 V, with a first-cycle coulombic efficiency of 92.09%.
[0218] The electrochemical test results of Examples 1-7 and Comparative Examples 1-2 are summarized in Table 2 as shown below.
[0219] Table 2 First cycle charge and discharge test results of the batteries in Examples 1-7 and Comparative Examples 1-2
[0220]
[0221] Note:
[0222] * The first cycle coulombic efficiency refers to the coulombic efficiency of the first cycle of battery charge and discharge. The calculation method of coulombic efficiency is as follows:
[0223]
[0224] The lower the first cycle coulombic efficiency, the better the sodium supplementation effect. Examples 1-5 verify that the sodium supplement according to the present invention has an excellent sodium supplementation effect. Compared with Comparative Examples 1-2, Examples 6-7 verify that the use of the sodium supplement according to the present invention can significantly improve the sodium supplementation effect of the prior art battery.
[0225] It can be seen that the novel material according to the present invention has excellent effects when applied in the field of sodium supplementation, and therefore has high commercial potential.
[0226] Although only sodium supplements are used as examples in the embodiments, due to the similarity between lithium ion batteries and sodium ion batteries, similar technical effects can be obtained by replacing the sodium in the embodiment materials with lithium or adjusting the relative amounts of sodium and lithium in the material of formula (I) of the present invention to apply it to the field of lithium supplementation or to lithium ion batteries. In addition, by replacing part of the sodium or all of the sodium in the embodiment materials with one or more elements in Group IA and Group IIA of the long-period periodic table, the present invention is applied to other batteries, such as potassium ion batteries, rubidium ion batteries, cesium ion batteries, magnesium ion batteries, calcium ion batteries, strontium ion batteries, barium ion batteries, or sodium ion batteries doped with one or more of lithium, potassium, rubidium, cesium, magnesium, calcium, strontium, and barium, and similar technical effects can also be obtained.
[0227] Although many of the numerical values and numerical ranges mentioned in this application are not described with the word "about", it should be understood that these numerical values and numerical ranges, like the numerical values and numerical ranges described with the word "about", can vary within the range of ±5% without departing from the spirit and scope of the present invention.
[0228] Unless there is a clear provision to the contrary, all technical and scientific terms used herein have the same meaning as generally understood by those skilled in the art to which the present invention belongs. Although some methods and materials are specifically described herein, similar or equivalent methods and materials described herein can also be used to implement the present invention although not specifically mentioned in this article. All publications, patent applications, patents and other references mentioned herein are all incorporated herein by reference. In the event of conflict, the definition in the application shall prevail. In addition, these materials, methods and examples are only illustrative and should not be considered as limiting the scope of protection claimed in the present application.
[0229] Although this specification contains many details of specific embodiments, these details should not be construed as limitations on the scope of any invention or what may be claimed, but rather as specific descriptions of features that may be specific embodiments of specific inventions. Certain features described in this specification in the context of separate embodiments may also be implemented in combination in a single embodiment, and various features described in the context of a single embodiment may also be implemented in multiple embodiments individually or in any suitable subcombination.
Claims
1. A material having a structure of formula (I): And 7n-x L x Fe 3n-y I y Oh 8n-a-b R a Q b (I) in: n is an integer selected from 1 to 10, 0≤x≤7n, 0≤y<3n, 0≤a<8n, 0≤b<8n, L is one or more elements selected from Group IA and IIA elements in the long-period periodic table, M is one or more metal elements selected from Groups IA-VIA, IB-VIIB and VIII in the long-period periodic table, R is one or more elements selected from Group VIIA elements in the long-period periodic table, Q is one or more selected from the elements of Group VIA in the long-period periodic table, and The atomic molar ratio of (Na+L):(Fe+M):(O+R+Q) is 7:3:
8.
2. The material according to claim 1, wherein formula (I) satisfies one or more of the following conditions: 1) n is selected from 1, 2 and 3; 2) x is 0 or 7n; 3)0≤y<3n / 2; 4)0≤a<4n; 5)0≤b<4n; 6) M is one or more selected from lithium, magnesium, aluminum, nickel, boron, scandium, titanium, vanadium, chromium, manganese, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, iridium and tin; 7) L is one or more selected from lithium, potassium, rubidium, cesium, magnesium, calcium, strontium, and barium; 8) R is one or more selected from fluorine, chlorine, bromine, and iodine; and 9) Q is one or more selected from sulfur, selenium and tellurium.
3. The material according to claim 1, which is selected from Na 7n Fe 3n O 8n 、Na 7n Fe 3n-y Ti y O 8n 、Na 7n Fe 3n-y Mn y O 8n 、Na 7n Fe 3n-y Al y O 8n 、Na 7n Fe 3n-y Co y O 8n 、Na 7n Fe 3n-y Cu y O 8n 、Na 7n Fe 3n-y Zn y O 8n 、Na 7n Fe 3n-y Ru y O 8n 、Na 7n Fe 3n-y Y y O 8n 、Na 7n Fe 3n-y B y O 8n 、Na 7n Fe 3n-y Mg y O 8n 、Na 7n Fe 3n-y Zr y O 8n 、Na 7n Fe 3n-y Ni y O 8n 、Na 7n Fe 3n O 8n-a F a or more than one of them, where n is 1 or 2, 0 < y < 3n, 0 < a < 8n.
4. The material according to claim 1, which is Na7Fe3O8 or Na 14 Fe6O 16 .
5. A method for preparing a material according to any one of claims 1 to 4, the method comprising the following steps: (a) mixing Fe2O3, Na2O and / or an oxide of L, and an optional dopant precursor to obtain a precursor mixture, wherein the stoichiometric ratio between Fe2O3 and the oxide of Na2O and / or L is 1:9-9:1, preferably 1:9-1:1, more preferably 1:6-1:2, wherein L is one or more elements selected from Groups IA and IIA of the long period periodic table; (b) heating the precursor mixture at a temperature of 100-1200° C., preferably 200-800° C., for 1-200 hours, preferably 20-100 hours under an inert atmosphere for high temperature sintering; (c) After cooling, the material is obtained. The method according to claim 5 , wherein the inert atmosphere is at least one selected from nitrogen, argon and helium.
7. The method according to claim 5 or 6, wherein the dopant precursor is one or more selected from the group consisting of oxides of M, sodium fluoride, sodium sulfide, iron fluoride and iron sulfide, wherein M is one or more selected from the group consisting of metal elements in Groups IA-VIA, IB-VIIB and VIII of the long period periodic table; preferably, the dopant precursor is an oxide of M, wherein M is one or more selected from the group consisting of lithium, magnesium, aluminum, nickel, boron, scandium, titanium, vanadium, chromium, manganese, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, iridium and tin.
8. A coated material comprising a core and a coating layer covering the surface of the core, wherein: The core comprises the material of any one of claims 1 to 4; The coating layer comprises one or more materials selected from the group consisting of metal fluorides, metal carbides, metal oxides, polymers, carbon, and combinations thereof; Optionally, there may or may not be a cavity between the coating layer and the core, and optionally, the coating layer is a continuous layer or a discontinuous layer.
9. The coated material according to claim 8, wherein the coating layer comprises one or more of a metal fluoride coating layer, a metal carbide coating layer, and a metal oxide coating layer, wherein the metal elements in the metal fluoride, the metal carbide and the metal oxide are independently selected from nickel, cobalt, aluminum, manganese, lithium, potassium, barium, iron, calcium, copper, zinc, titanium, magnesium, zirconium, strontium, chromium, tin, antimony, tungsten, niobium, molybdenum, vanadium, palladium, bismuth, cesium, hafnium, tantalum, polonium, gallium, indium, thallium, yttrium, scandium, lanthanide elements and combinations thereof; preferably, the coating layer comprises a metal oxide coating layer, wherein the metal elements in the metal oxide are selected from nickel, cobalt, aluminum, manganese, lithium, potassium, barium, iron, calcium, copper, zinc, titanium, magnesium, zirconium and combinations thereof.
10. The coated material according to claim 8 or 9, wherein the coating layer comprises a polymer coating layer, a carbon coating layer and a combination thereof, wherein the polymer comprises one or more selected from the following: polypyrrole polymers and modified products thereof, polythiophene polymers and modified products thereof, polyamide polymers and modified products thereof, polyethylene oxide polymers and modified products thereof, polyvinylidene fluoride polymers and modified products thereof, polyacrylate polymers and modified products thereof, polyacrylonitrile polymers and modified products thereof, polyether polymers and modified products thereof, polysiloxane polymers and modified products thereof or polyanion single ion conductor type polymers and combinations thereof.
11. A composite material comprising a first material and a second material, wherein: The first material comprises the material according to any one of claims 1 to 4; The second material is a battery active material different from the first material.
12. The composite material according to claim 11, wherein the second material is at least one sodium-containing positive electrode active material selected from Prussian blue, polyanion compounds, transition metal layered oxides, and sodium-containing organic compounds; preferably, the second material is selected from Na(Ni x’ Fe y’ Mn 1-x’-y’ )O2, Na 0.74 (Ni x’ Fe y’ Mn 1-x’-y’ )O2, Na 0.67 (Ni x’ Mn y’ Ti 1-x’-y’ )O2, Na 0.67 (Ni x’ Mn y’ Zn z’ Cu 1-x’-y’-z’ )O2, Na2M’[Fe(CN)6], NaVPO4F, Na2FePO4F, Na3V2(PO4)3, Na2Fe2(SO4)3, NaTiO2, NaMnO2, NaFeO2, NaCoO2, NaNiO2, Na2C6O6 and combinations thereof, where 0 < x’ < 1, 0 < y’ < 1, 0 < z’ < 1, and M’ is selected from Fe, Co, Mn, Ni, Cu and combinations thereof; more preferably, the second material is selected from NaNi 1 / 3Fe 1 / 3 Mn 1 / 3 O2, Na 0.74 Ni 1 / 4 Fe 1 / 4 Mn 1 / 2 O2 and combinations thereof. 13 . The composite material according to claim 11 , wherein the weight ratio of the first material to the second material is 1:30 to 30:
1.
14. The composite material according to claim 11 or 12, wherein the first material further comprises one or more additional materials selected from the following: NaN3, Na2O, Na2O2, Na2C2O4, Na2CO3, Na3C6H5O7, Na2C2O2N2, Na2C2N4, Na2C4H5NO4, Na3C7H8NO6 and combinations thereof.
15. A method for preparing a composite material according to any one of claims 11 to 14, the method comprising the step of compounding a first material and a second material in the form of mixing and / or coating, wherein the mixing preferably comprises the step of mixing the first material and the second material by stirring and / or grinding, and the coating preferably comprises the step of attaching the second material to the outside of the first material.
16. A positive electrode active material comprising one or more of the material according to any one of claims 1 to 4, the coated material according to any one of claims 8 to 10, the composite material according to any one of claims 11 to 14, and a combination thereof. 17 . A positive electrode for a battery, comprising the positive electrode active material according to claim 16 , an optional conductive agent, and an optional binder.
18. The positive electrode of a battery according to claim 17, wherein the binder is selected from at least one of polyvinylidene fluoride, polyvinylidene chloride, polytetrafluoroethylene, polyethylene oxide, polyvinylidene chloride-hexafluoropropylene, polyacrylic acid, polyacrylonitrile, polyacrylamide, polyamide, polyamideimide, polymethyl methacrylate, polycarbonate, carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene-butadiene copolymer, sodium alginate, styrene-butadiene rubber and combinations thereof, and preferably the amount of the binder is 0.5-10 wt % based on the total weight of the positive electrode of the battery; and / or the conductive agent is selected from at least one of carbon black, acetylene black, Ketjen black, conductive graphite, carbon fiber, carbon nanotubes, graphene, graphene oxide, reduced graphene oxide and combinations thereof, and preferably the amount of the conductive agent is 0.5-10 wt % based on the total weight of the positive electrode of the battery.
19. An electrode sheet, comprising one or more of the material described in any one of claims 1 to 4, the coated material described in any one of claims 8 to 10, the composite material described in any one of claims 11 to 14, and a combination thereof, and a conductive substance; the electrode sheet preferably comprises a coating, and the coating comprises one or more of the material described in any one of claims 1 to 4, the coated material described in any one of claims 8 to 10, the composite material described in any one of claims 11 to 14, and a combination thereof.
20. A diaphragm comprising one or more of the material described in any one of claims 1 to 4, the coated material described in any one of claims 8 to 10, the composite material described in any one of claims 11 to 14, and combinations thereof, and a polymer material; the diaphragm preferably comprises a coating, and the coating comprises one or more of the material described in any one of claims 1 to 4, the coated material described in any one of claims 8 to 10, the composite material described in any one of claims 11 to 14, and combinations thereof.
21. An electrochemical device comprising at least one of the positive electrode active material according to claim 16, the battery positive electrode according to any one of claims 17-18, the electrode sheet or separator according to claim 19, and a combination thereof.